Scientific and Educational Potential as a Factor in Ensuring the Economic Security of the State in Terms of the Digital Development Intensification: Analysis and Assessment for the BRICS Countries - Elena A. YAKOVLEVA; Olga N. GORBUNOVA; Tigran L. OGANESYAN; Olga S. SHURUPOVA; Evgeniya K. KARPUNINA (Communications of International Proceedings, 2020)
The purpose of the research is to reveal the specifics and conduct a comprehensive analysis of the scientific and educational potential and the system of ensuring the economic security of the state as a basis for strengthening the positions of the BRICS countries in the global competitive space. The authors identified the structural features of the country's scientific and educational potential and identified its components (personnel, material and technical, economic, organizational and managerial), as well as assessed the development dynamics (within the BRICS group and in comparison, with some developed countries). The authors systematized economic security threats from the scientific and educational potential. It is concluded that China and Russia among the BRICS countries have a more stable position in terms of economic security, due to the state of their scientific and educational potential. The authors proposed tools to reduce economic security threats of the state from the scientific and educational potential development.
Keywords: economic security of the state; scientific and educational potential; BRICS; integration processes; digital economy